Accuracy of a local positioning system for time-series speed and acceleration and performance indicators in game sports - Fuchs, P. X.; Chou, Y. C.; Chen, W. -H.; Fiolo, N.; Shiang, T.-Y. (Sports Biomechanics, 2023)
The objective was to determine the reliability and validity of a local positioning system (LPS) promising high accuracy at reduced product costs. Fifty-five random static positions in a gym (54.8 × 26.0 m) were obtained 10 times via LPS (50 Hz) and measuring tape. An athlete`s LPS-derived peak and time-series speed and acceleration during dynamic movements (n = 80) were compared with Vicon (100 Hz). Reliability and validity were assessed via Intraclass and Concordance Correlation Coefficients (ICC/CCC), root mean square errors, Bland-Altman plots, and analysis of variance. ICC3,1 (=0.999) and CCC (0.387-0.999) were calculated for static positions (errors <0.22 m). CCC for time-series speed and acceleration, and peak speed, acceleration, and deceleration were 0.884-0.902, 0.777-0.854, 0.923, 0.486, and 0.731, respectively. Errors were larger in time-series acceleration (14.37 ± 3.77%) than in speed (11.99 ± 5.78%) (2p = 0.472, p < 0.001) and in peak acceleration (28.04 ± 14.34%) and deceleration (25.07 ± 14.90%) than in speed (7.34 ± 6.07%) (n2p = 0.091, p < 0.01). LPS achieved excellent reliability and moderate-to-excellent validity of time-series speed and acceleration. The system accurately measured peak speed but not peak acceleration and deceleration. The system is suitable for analyses based on instantaneous speed and acceleration in game sports (e.g., energy estimations).